2015
DOI: 10.1001/jamainternmed.2015.1657
|View full text |Cite
|
Sign up to set email alerts
|

Informed Decision Making for Percutaneous Coronary Intervention for Stable Coronary Disease

Abstract: IMPORTANCE Patients with stable coronary disease undergoing percutaneous coronary intervention (PCI) are frequently misinformed about the benefits of PCI. Little is known about the quality of decision making before angiography and possible PCI. OBJECTIVE To assess the quality of informed decision making and its association with patient decisions. DESIGN, SETTING, AND PARTICIPANTS We performed a cross-sectional analysis of recorded conversations between August 1, 2008, and August 31, 2012, among adults with kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…4,10 Placebo effects are known to be larger for invasive than non-invasive treatments.11 Interventional cardiologists and patients with stable angina often think that PCI offers symptomatic relief. 12 Additionally, cardiologists present a decisive approach to diagnosis and treatment, which can lead to an enhanced placebo effect. 13 In the absence of blinding, the effect size of PCI on symptomatic endpoints can be overestimated because of the addition of the placebo effect to the true physiological effect of intervention.14 In all previous trials, both investigators and patients were aware of the treatment allocation.…”
Section: Introductionmentioning
confidence: 99%
“…4,10 Placebo effects are known to be larger for invasive than non-invasive treatments.11 Interventional cardiologists and patients with stable angina often think that PCI offers symptomatic relief. 12 Additionally, cardiologists present a decisive approach to diagnosis and treatment, which can lead to an enhanced placebo effect. 13 In the absence of blinding, the effect size of PCI on symptomatic endpoints can be overestimated because of the addition of the placebo effect to the true physiological effect of intervention.14 In all previous trials, both investigators and patients were aware of the treatment allocation.…”
Section: Introductionmentioning
confidence: 99%
“…Many clinicians feel they already perform SDM regularly; yet, data suggest that attitudes are often not aligned, 35,36 and there is little evidence of proficiency in SDM skills. 37 Importantly, the high scores on 2 items from the OPTION scale that focused on patient education suggested that the decision aid was often used as an educational pamphlet rather than a tool to facilitate a shared conversation. This trial suggests that although specialists may report that they already perform SDM, this may be because of a gap in knowledge of how this process is distinct from patient education.…”
Section: Discussionmentioning
confidence: 99%
“…4 Finally, recent evidence suggests that stable ischemic heart disease patients appropriately informed on the risk/benefit of various treatment options and their alternatives may lead to preferential choice of medical management over angiography and PCI. 19 Our study should be interpreted in the context of the following limitations. First, as this was a claims-based analysis, we were not able to determine or adjust for the angina severity (i.e., Canadian Cardiovascular Society angina class angina class) or burden of coronary atherosclerosis.…”
Section: A N U S C R I P Tmentioning
confidence: 97%